FILOSOFI URIP IKU URUP PADA MASYARAKAT JAWA: PENDORONG KOHESIVITAS KELOMPOK PENGUAT KEHARMONISAN MASYARAKAT PERUMAHAN KABUPATEN KEDIRI - Nadya Ratu Amala (Universitas Negeri Surabaya, 2022)
Urip Iku Urup Javanese philosophy has a value that builds social interaction between individuals and other individuals. So that in this social interaction solidarity is established in building community harmony, especially in a community group in the Housing environment. This study aims to examine the cohesiveness of groups strengthening the harmony of residential communities through Javanese philosophy. This study was conducted using a descriptobe qualitative method by conducting observation and community interviews in Kediri Regency, especially in the housing of Sukorejo Indah located in Katang Village, Ngasem Distric, Kediri Regency. The results of this study show that Javanese philosophy can be the driving force behind the cohesiveness of community life, Java has not implemented Javanese philosophy in community life, there are still many housing units whose people still apply the Javanese philosophy “Urip Iku Urup” in community activities. Although in Javanese philosophy practice every region in Kediri Regency has a difference, some still uphold that philosophy. Teherefote, awareness in establishing harmony between neighbors is still maintained so that harmony can be achieved of every community in Sukorejo Indah Housing.